2021
DOI: 10.7150/jca.62491
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of PRR11 affects the proliferation, migration and invasion of osteosarcoma by inhibiting the Wnt/β-catenin pathway

Abstract: This study aim to explore the effect of down-regulation of PRR11 (proline-rich protein 11) on the proliferation, invasion, migration, Wnt/β-catenin signaling pathway and EMT of osteosarcoma cells. Methods: Immunohistochemical staining, fluorescent quantitative PCR and western blotting were used to detect the expression level of PRR11 in osteosarcoma tissues and osteosarcoma cells. After SiRNA down-regulated the expression level of PRR11, CCK8 was used to detect cell proliferation ability, Transwell chamber to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…As an important intracellular transcription factor, c-myc promotes glycolysis by transactivating and promoting the expression of genes related to glycolysis ( Gruning et al, 2010 ; Han et al, 2012 ). Furthermore, as the target of several oncogenes or tumor suppressor genes, c-myc participates in regulating many signal pathways, such as MEK-ERK, Wnt/β-catenin, PI3K/AKT/mTOR, and STAT3/c-myc ( Han et al, 2012 ; Li K. et al, 2021 ; Tang et al, 2022 ). In 2012, Han et al (2012) found that c-myc overexpression in OS significantly enhanced the invasive ability of OS cells by promoting the MEK-ERK pathway.…”
Section: The Glycolysis In Osteosarcomamentioning
confidence: 99%
“…As an important intracellular transcription factor, c-myc promotes glycolysis by transactivating and promoting the expression of genes related to glycolysis ( Gruning et al, 2010 ; Han et al, 2012 ). Furthermore, as the target of several oncogenes or tumor suppressor genes, c-myc participates in regulating many signal pathways, such as MEK-ERK, Wnt/β-catenin, PI3K/AKT/mTOR, and STAT3/c-myc ( Han et al, 2012 ; Li K. et al, 2021 ; Tang et al, 2022 ). In 2012, Han et al (2012) found that c-myc overexpression in OS significantly enhanced the invasive ability of OS cells by promoting the MEK-ERK pathway.…”
Section: The Glycolysis In Osteosarcomamentioning
confidence: 99%
“…Mechanically, PRR11 knockdown decreased β-catenin and p-GSK-3β and increased p-β-catenin and GSK-3β, thus inactivating Wnt/β-catenin signaling. In addition, PRR11 knockdown also increased the expression of E-cadherin, but reduced vimentin and fibronectin in the EMT signaling [ 21 ]. Above all, PRR11 might be an independent and reliable biomarker and therapeutic target for osteosarcoma patients.…”
Section: Oncogenic Role Of Prr11 In Various Malignanciesmentioning
confidence: 99%
“…Subsequently, in vitro and in vivo models were utilized for evaluation of PRR11 in tumorigenesis. In vitro, cellular proliferation and cell-cycle progression were evidently boosted by PRR11 in TSCC, ESCC, NSCLC, BRCA, GC, CRC, HCC, HCCA, Pancreatic cancer, Ovarian cancer and Osteosarcoma [ 4 , 5 , 7 , 8 , 10 , 12 , 13 , 14 , 16 , 19 , 21 ]. Similarly, in in vivo models, PRR11 promoted xenograft tumor growth in tumor size, weight and Ki-67 expression in TSCC, NSCLC, GC, CRC, HCC and Ovarian cancer [ 2 , 6 , 8 , 9 , 11 , 13 , 19 , 20 ].…”
Section: Biological and Clinical Significance Of Prr11 In Human Cancersmentioning
confidence: 99%
See 2 more Smart Citations